Effect of exopolysaccharides produced by dairy starter cultures on biofilms formed on reverse osmosis membranes - Nuria Garcia-Fernandez; Ashraf Hassan; Sanjeev Anand (JDS Communications, 2021)
Two different cheese starter cultures producing exopolysaccharides (EPS+: Streptococcus thermophilus strain ST3534 and Lactococcus lactis ssp. cremoris strain JFR+) and their isogenic EPS-negative (EPS−: S. thermophilus strain ST5842 and L. lactis ssp. cremoris strain JFR–) variants were used to study the attachment of bacterial cells in the absence of growth (at 4°C) and the resultant biofilm formation on reverse osmosis membranes (at 30 or 35°C). We used M17 broth and a 10% solution of whey protein concentrate (with 35% protein) as growth media for biofilm development under static conditions. As expected, ST3534 (EPS+) showed significantly greater cell counts within biofilms than ST5842 (EPS−). In the absence of growth, however, cells of these 2 isogenic Streptococcus strains attached to the membrane in similar numbers. In contrast, JFR+ counts were significantly lower than those of JFR– under all conditions. These findings indicate that the EPS produced by S. thermophilus may play a greater role in building up the 3-dimensional structure of the biofilm, rather than only assisting during initial attachment of the cells to the membrane, whereas the EPS produced by L. lactis ssp. cremoris hampered both initial attachment to the membrane and biofilm formation. Although no differences were observed in the surface charge of the cells between the 2 EPS-producing cultures, surface hydrophobicity was associated with the different adhesive properties of these microorganisms. In conclusion, our results exclude the hypothesis that all EPS-producing starter cultures have an advantage in regard to their ability to form biofilm on membrane separation surfaces. In contrast, variations between different EPS, with hydrophobicity being an important influencing feature, modify adhesive behavior to reverse osmosis membranes.